Love and Self-Discovery: The Journey of Sexuality in Bernardine Evaristo’s Mr Loverman - S. POONGUZHALI; Dr.K. THAYALAMURTHY (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This article provides an analysis of the extensive hardships faced by the gay character Barry, encompassing various dimensions, including physical, emotional, and societal aspects. Barry, a male individual hailing from the Caribbean, experiences the adverse effects of social stigma due to his sexual orientation. The primary tension of this novel is centred on the exploration of Barry's sexual orientation; his quest for love and self-discovery are prominent themes in this novel. Barry's reluctance to disclose his true sexual orientation is rooted in his fear of rejection and condemnation from his Caribbean community. Despite the fact that he has loved Morris since childhood, he has kept this a secret throughout his entire existence. Throughout his life, he has constantly lived with a fear of judgment by society; he has known his sexuality since childhood. However, he has chosen to conceal his identity from his family and acquaintances for an extended period of time, primarily due to prevailing societal and cultural norms and expectations. The central conflict of Barry hiding his sexuality in the novel can serve as a powerful and relatable theme, as it addresses issues related to identity, societal expectations, and personal growth.